2019
DOI: 10.1155/2019/5353825
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Optimization of 6‐DOF Parallel Manipulator for Desired Total Orientation Workspace

Abstract: A desired total orientation workspace for a parallel manipulator is usually an essential requirement in a practical application. At present, for the multiobjective optimization method of 6-DOF parallel manipulator for desired total orientation workspace, it is needed to predefine maximal and minimal lengths of the legs to serve as the constraint, and then the numerical method is used to solve the length of the legs and judge whether the solved maximal and minimal leg lengths meet the constraint. Predefining ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Industrial Advances in Machining Parameters particle swarm Optimization for materials were done using Response Surface Methodology (Lmalghan et al, 2018). Further, multiobjective optimization is used for 6-DOF Parallel Manipulator for setting total Workspace (Qiang et al, 2019). Recently, parametric performances of parallel structures with 3 or higher degrees of freedom are being controlled to get maximum dexterity (Xie et al, 2019).…”
Section: Literaturementioning
confidence: 99%
“…Industrial Advances in Machining Parameters particle swarm Optimization for materials were done using Response Surface Methodology (Lmalghan et al, 2018). Further, multiobjective optimization is used for 6-DOF Parallel Manipulator for setting total Workspace (Qiang et al, 2019). Recently, parametric performances of parallel structures with 3 or higher degrees of freedom are being controlled to get maximum dexterity (Xie et al, 2019).…”
Section: Literaturementioning
confidence: 99%
“…Kim ve arkadaşları 6 serbestlik derecesine sahip mekanizmada herhangi bir dönme ekseninde, sınırsız 360 derece sürekli dönüş ve sonlu X, Y ve Z ekseni öteleme hareketini sağlama üzerinde çalışma yapmışlardır [5]. Qiang ve arkadaşları toplam oryantasyon çalışma alanı için 6-SD paralel manipülatörün çok amaçlı optimizasyonunu gerçekleştirmişlerdir [6]. İnner ve Küçük, genel stewart platform mekanizmalarının tasarım, analiz ve benzetiminin yapılabileceği STEWSIM isimli simülasyon aracını geliştirmişlerdir [7].…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…In [12,13], typical non-dimensional performance indices were used to optimize the geometric parameters of a 3-DOF parallel kinematic structure. Considering the performance criteria of the 6-DOF parallel manipulators, a multi-objective optimization is formulated in [7,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Stiffness, precision, and workspace [6,7] are typical performance indexes of a mechanism. Though many studies have shown that the precision of CPP is able to meet the needs, in most application scenarios, the limited stiffness and workspace of CPPs still confine the scope of their application.…”
Section: Introductionmentioning
confidence: 99%